ANALISIS PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP FINANCIAL DISTRESS - Agus Elyanto, Alvin; Syafruddin, Muchamad (Diponegoro Journal of Accounting, 2013)
This study aimed to examine the effect of audit committee characteristics such as the size of the audit committee, the composition of non-executive directors in audit committee, the number of audit committee meetings, and the number of financial literacy in the audit committee of the occurrence of financial distress. The population in this study is an entire company (non-banking) listed in the Indonesia Stock Exchange in 2010 and 2011. Samples were taken by purposive sampling. The criteria of financial distress company is a company with a negative net income in the financial reporting period. Total sample used is 84 companies consist of 42 financial distress companies and 42 non-financial distress companies with the similarity in the industry and accounting reporting period. This study uses logistic regression as statistical tools. The result showed that variable the number of audit committee meetings and the number of financial literacy on the audit committee have a negative and significant relationship with the probability of financial distress, while variable the size of the audit committee and the composition of non-executive directors in audit committee have negative but not significant relationship with the probability of financial distress.